Effects of season-dependent irradiance levels and nitrogen-deficiency on photosynthesis and photoinhibition in field-grown rice (Oryza sativa) - Chen, Yizhu; Murchie, Erik H.; Hubbart, Stella; Horton, Peter; Peng, Shaobing (Wiley, 2003)
Photoinhibition and acclimation of photosynthesis in rice plants grown under N‐sufficient (NS) and N‐deficient (ND) field conditions were investigated during the tropical wet (WS) and dry (DS) seasons in the Philippines. Diurnal patterns of CO2 assimilation were examined. There was a transient peak in CO2 assimilation in the leaves of the NS plants in the early morning during the DS and the WS, which was not seen in the ND plants in either season. ND leaves had lower Ribulose bisphosphate carboxylase/oxygenase (Rubisco) contents and lower chlorophyll contents. A lowered quantum yield of photosystem II (φPSII) was observed in the ND plants at an intermediate irradiance though no differences between N treatments were seen at high irradiance. Analysis of carotenoids indicated a small increase in the de‐epoxidation state of the xanthophyll cycle (DES) at mid‐day in the ND leaves compared to NS. Photoinhibition was greater in ND leaves when incident mid‐day irradiance was increased by altering the leaf angle. Although Rubisco contents were lower in ND plants, photosynthesis in situ did not decline proportionally. For NS plants, Chlorophyll content, but not Rubisco content, was season‐dependent and results are discussed in terms of the interaction between irradiance use and N content of rice leaves.